Health expectancies of the elderly population in Sri Lanka - Weeratunga, M.K. (University of Colombo, Sri Lanka., 2019)
Life expectancy at birth has continuously increased in most countries over the last century. As such, the life expectancy of Sri Lanka's elderly population shows an increasing trend. Therefore, whether the additional years of life are also accompanied by good health has become a subject of intense interest. Healthy life expectancy of older Sri Lankans is an emerging issue due to the prevalence of various chronic diseases among the elderly population. The main objective of this study is to estimate the healthy life expectancy of the elderly population in Sri Lanka. This study was largely based on the healthy life expectancy proposed by the Sullivan Method. It used both primary and secondary data. The morbidity information used in applying the Sullivan method comes from the 2012 Census and healthy life expectancy is calculated using the life tables constructed by the Department of Census and Statistics for the period 2000-2002 and 2011-2013. In order to supplement the analysis, a sample survey of 300 elderly people was carried out in the Gampaha district. Furthermore, the sample survey findings supplemented the analysis performed using secondary data. This study found that both elderly men and women have spent a considerable time living with disability because of deterioration in their health. When the difference between total life expectancy and health expectancy is investigated, the study found that in 2001 men were in a disabled state for 0.8 years compared to 0.94 years for women on average. Furthermore, this difference has drastically increased in 2012, with 5.24 and 7.32 years for men and women, respectively. These results show that women are in a more morbid state compared to men after 11 years. This further reveals that lack of financial security makes elderly people vulnerable to unhealthy situations, especially elderly women.
Keywords: elderly population, heathy ageing, healthy life expectancy, life expectancy